LoRaWISEP+: A Comprehensive Tool for Strategic Gateway Placement in LoRaWAN Networks - Abreu, Pedro F. F.; Mendes, Luís H. de O.; Sarmento Neto, Geraldo A.; Silva, Thiago A. R. da; Veloso, Artur F. da S.; Leão, Erico; dos Reis Junior, José V. (Anais Estendidos do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC); 2024: Anais Estendidos do XIV Simpósio Brasileiro de Engenharia de Sistemas ComputacionaisDO - 10.5753/sbesc_estendido.2024.243700, 2024)
The Internet of Things has revolutionized device interconnectivity, with Low Power Wide Area Networks (LPWAN) enabling long-range communication with minimal energy consumption. Within this context, LoRaWAN is widely recognized as an efficient and robust technology for LPWAN networks. However, strategic gateway deployment remains a challenging for optimizing network performance. In this way, this paper issue proposes LoRaWISEP+, an enhanced version of the LoRaWISEP system, consisting of a comprehensive tool designed to improve the deployment process of LoRaWAN gateways. This solution incorporates additional clustering algorithms, such as K-Medoids (KMD) and Fuzzy C-Means (FCM), and a redesigned userfriendly interface, facilitating optimal placement of gateways and improving overall network coverage and reliability. In order to validate the new features of the proposed tool, a thorough evaluation was conducted using real-world deployment scenarios. Results demonstrate that different clustering algorithms exhibit strengths in specific characteristics, such as FCM being more suitable for lower energy consumption and K-Means (KM) being more suitable for higher transmission rates. This makes LoRAWISEP+ an enabling tool for optimizing network planning according to the most beneficial characteristic for the user.